Tata Kelola Konflik Keberadaan Pabrik Gula Camming Terhadap Kehidupan Sosial Masyarakat di Desa Wanuawaru - Usman, Jaelan; Riswandi, Muhammad; Setiawati, Budi; Hawing, Hardianto (Kybernology : Journal of Government Studies, 2021)
The purpose of this study is to effectively manage conflict, avoid and prevent conflict from arising, and determine the effects of conflict management on Wanuawaru Village's social life in relation to the presence of a camming sugar mill. A case study technique is the kind of research that is employed. The results of the study highlighted conflict governance related to the existence of the Camming sugar factory in the aspect of social life, focusing on four main indicators. First, Environmental Governance in Camming Sugar Factory Waste Management is discussed through four approaches to conflict resolution strategies. The first approach is Avoiding, where all parties work together to prevent conflict. Second, Accommodating refers to handling conflicts by considering various incoming opinions, by gathering and resolving conflicts inclusively. The third approach, Compromising, emphasizes taking into account the opinions and interests of all parties. The negotiation process is engaged to address conflicts that may affect people's social lives, by reaching an agreement that benefits all parties. Finally, Collaboration as the fourth approach describes how both parties engage on an ongoing basis to resolve existing conflicts.